2017
DOI: 10.1039/c6cy02521h
|View full text |Cite
|
Sign up to set email alerts
|

Metal dimer sites in ZSM-5 zeolite for methane-to-methanol conversion from first-principles kinetic modelling: is the [Cu–O–Cu]2+motif relevant for Ni, Co, Fe, Ag, and Au?

Abstract: Reaction energy landscapes for the direct conversion of methane to methanol over ZSM-5 for Cu, Ni, Co and Fe dimer sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 68 publications
5
50
0
1
Order By: Relevance
“…Actually, in nature, methanotrophic bacteria do express methane monooxygenase (a kind of metalloenzyme containing dicopper or diiron active sites) to convert methane into methanol at ambient temperature, despite the high energy needed (435 kJ mol −1 ) to split the C-H bond [ 65 , 66 , 67 ]. It is remarkable that ongoing research carried out by several research groups (see, for instance, [ 68 , 69 , 70 , 71 ]) has shown that several copper-exchange zeolites can convert methane into methanol at a relatively mild temperature (150–200 °C), and there is evidence that in Cu-ZSM-5, the catalytic center involves a μ-oxo dicopper complex [ 72 , 73 ]; however, the mechanistic details are yet to be elucidated. Finally, we wish to mention earlier work by several authors [ 74 , 75 , 76 ] showing that Cu-ZSM-5 adsorbs dinitrogen-forming bridged Cu + ···N-N···Cu + complexes on dual Cu + sites.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, in nature, methanotrophic bacteria do express methane monooxygenase (a kind of metalloenzyme containing dicopper or diiron active sites) to convert methane into methanol at ambient temperature, despite the high energy needed (435 kJ mol −1 ) to split the C-H bond [ 65 , 66 , 67 ]. It is remarkable that ongoing research carried out by several research groups (see, for instance, [ 68 , 69 , 70 , 71 ]) has shown that several copper-exchange zeolites can convert methane into methanol at a relatively mild temperature (150–200 °C), and there is evidence that in Cu-ZSM-5, the catalytic center involves a μ-oxo dicopper complex [ 72 , 73 ]; however, the mechanistic details are yet to be elucidated. Finally, we wish to mention earlier work by several authors [ 74 , 75 , 76 ] showing that Cu-ZSM-5 adsorbs dinitrogen-forming bridged Cu + ···N-N···Cu + complexes on dual Cu + sites.…”
Section: Discussionmentioning
confidence: 99%
“…By using this basis set, the effect of occupied atomic orbital and valence atomic orbital have been considered and, a polarisation p-function on all hydrogen atoms was applied. Therefore, this basis set could provide reasonable accuracy with acceptable computational cost, which has been heavily used in DFT calculation for ZSM-5 [51][52][53] . During geometry optimisation, the tolerances of energy, gradient and displacement convergence were 2 × 10 −5 Ha, 4 × 10 −3 Ha Å −1 and 5 × 10 −3 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is of great interest to comparatively investigate materials containing different types of copper species. Moreover, unlike many other metal-zeolite reaction systems, no reaction intermediates, presumably such as surface-bound methyl or methoxy groups [20], have been directly observed for copper-modified small-pore zeolites under DCMM reaction conditions.…”
Section: Introductionmentioning
confidence: 87%